The acceptability of mass administrations of anti-malarial drugs as part of targeted malaria elimination in villages along the Thai–Myanmar border. (December 2016) - Kajeechiwa, Ladda; Thwin, May; Shee, Paw; Yee, Nan; Elvina, Elvina; Peapah, Peapah; Kyawt, Kyawt; Oo, Poe; PoWah, William; Min, Jacqueline; Wiladphaingern, Jacher; Seidlein, Lorenz; et al.
Abstract Background A targeted malaria elimination project, including mass drug administrations (MDA) of dihydroartemisinin/piperaquine plus a single low dose primaquine is underway in villages along the Thailand Myanmar border. The intervention has multiple components but the success of the project will depend on the participation of the entire communities. Quantitative surveys were conducted to study reasons for participation or non-participation in the campaign with the aim to identify factors associated with the acceptance and participation in the mass drug administrations. Methods The household heads in four study villages in which MDAs had taken place previously were interviewed between January 2014 and July 2015. Results 174/378 respondents (46 %) completed three rounds of three drug doses each, 313/378 (83 %) took at least three consecutive doses and 56/378 (15 %) did not participate at all in the MDA. The respondents from the two villages (KNH and TPN) were much more likely to participate in the MDA than respondents from the other two villages (HKT and TOT). The more compliant villages KNH and TPN had both an appearance of cohesive communities with similar demographic and ethnic backgrounds. By contrast the villages with low participation were unique. One village was fragmented following years of armed conflict and many respondents gave little inclination to cooperate with outsiders. The other village with low MDA coverage was characterised by a high percentage of short-term residents with little interest in community interventions. A universal reason for non-participation in the MDA applicable to all villages was an inadequate understanding of the intervention. Conclusions It is unlikely that community engagement can unite fragmented communities in participating in an intervention, which benefits the community. Understanding the purpose and the reasons underlying the intervention is an important pre-condition for participation. In the absence of direct benefits and a complete understanding of the indirect benefits trust in the investigators is critical for participation.